Integrating mobile game application in enhancing students' willingness to communicate in English - Anna Lynn Abu Bakar; Irma Wani Othman; Nadiawati Mahmood; Mohammad Aqmal Hafidz Musa (Global Academic Excellence, 2022)
English is an important communication medium for Malaysians, particularly in higher education and business. As a result, substantial effort has been invested in producing students who can communicate effectively in a variety of social and professional settings. It is believed that, as a result of the new learning standard, mobile game applications offer a greater opportunity to enhance language learning, particularly English, for Gen-Z students. One of the mobile gaming applications utilised for this study was Languinis, an original, free word puzzle mobile game. An administered questionnaire was administered to 120 ESL students as part of a mixed-methods approach. A semi-structured interview with 10 ESL students was also conducted. The data of the investigation revealed that few pupils are familiar with the Languinis word game. Nonetheless, the finding also revealed that the students enjoyed using the mobile game application to improve their vocabulary, which they then utilised in their spoken interactions. As a result, their Willingness to Communicate (WTC) in English has improved.